The Influence Of Palm Oil Fuel Ash And Metakaolin On The Strength Of Concrete And Crack Resistance Of Reinforced Concrete Beam A Review - Nyandau, Shaneez Christie (Universiti Sains Malaysia, 2021)
An ordinary Portland cement has been used in the production concretes, it is an important material to be kept in check due to its nature to react with every substance present. During the production of cement, a significant amount of carbon dioxide is emitted from the clinker production in rotary kiln and high energy requirement of the overall production processes. Such an event can be prevented by replacing the part of cement with Metakaolin (MK) and Palm Oil Fuel Ash (POFA). Aside from being a cementitious alternative, the materials can also contribute to a greener environment and more sustainable building, as POFA is available in Malaysia and may be used to substitute cement and minimize pollution. The study assesses the effect of MK and POFA on the concrete in terms of compressive strength and cracks pattern of the reinforced concrete beam based on relevant previous studies. From the research, the compressive strength of concrete containing MK and POFA was higher than the control mix with the percentage of improvement in the range of 0.8% to 78.2% for MK and 0.5% to 14% respectively. The optimum content of MK and POFA is between the range of 10% to 15% and 10% to 20% respectively to achieve high strength of concrete. Other than that, the inclusion of MK to the concrete mix improves the strength of reinforced concrete beams and reduces cracks on the surface of reinforced concrete beams, whereas the inclusion of POFA to the concrete mix increases cracks on reinforced concrete beams. The cracks appeared within the flexure zone of every beam containing the MK and POFA. From this study, it was also found that the fineness of MK and POFA has a significant influence on the mechanical properties of concrete.